The Legacy of the Soviet Union
XII, 275 p.
Keywords: The Legacy of the Soviet Union offers a distillation by a group of eminent scholars of their experience of the post-Soviet years. Analysis of the post-Soviet landscape is accompanied by meditations on the impact of the post-Soviet transition on both policy-makers and academics. The book therefore examines both assumptions of 'transition' and reconsiders the experience of Soviet communism in the light of its demise.